KEDUDUKAN BADAN ARBITRASE SYARIAH NASIONAL DALAM HUKUM NASIONAL INDONESIA - Bincang Bincang (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTIONThe terms of the Indonesian legal system (National), the existence of Arbitration National Sharia (BASYARNAS) as an arbitration institution Islam has a legitimacy that is very strong due to positive law currently allows some other institutions outside the judiciary generally become a referee / judge in the settlement of disputes the parties. This can be seen in Law No. 4 of 2004 Article 3, paragraph 1 of the main points of the judicial authorities and Law No. 30 1999 on Arbitration and Alternative dispute resolution between the parties. Indonesian National Arbitrage Agency. Both have the same authority that resolve civil disputes by means of peace, but BASYARNAS in running its authority based on the Quran and Al Hadith.BASYARNAS has authority in solving business disputes the parties in accordance with the regulatory procedure menangai BASYARNAS namely in terms of disputes arising in relation to trade, industry, finance, services, etc. where the parties agree to submit the settlement to BASYARNAS. But BASYARNAS not authorized to settle disputes like inheritance, grants, divorce etc. in because it is within its jurisdiction.